OPTIMIZATION OF IRRIGATION SCHEDULING ON THE BASIS OF IW/CPE RATIOS FOR WHEAT - RAJANEE SALUNKHE,; M. M. DESHMUKH,; S. B. WADATKAR, (The Bioscan, 2015)
The research was conducted at the Wheat Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola to optimize different IW/CPE irrigation schedules with optimum water use efficiency of wheat crop (variety AKAW- 4627). The experiment was carried out in 2011-12 and 2012-13 during December to March in randomized block design with five irrigation treatments and four replications. Treatments includes irrigation at IW/CPE ratios at 0.6 (I 1 ), 0.8 (I 2 ), 1.0 (I 3 ), 1.2 (I 4 ) and Control treatment with six irrigations at critical growth stages of wheat (I 5 ). Irrigation scheduling at IW/CPE=1.2 (I 4 ) recorded significantly highest grain yield 39.37 q/ha and 39.44 q/ha in 2011-12 and 2012-13 respectively compared to rest of treatment. Water use efficiency recorded in treatment I 3 i.e. 0.67 q/ha-cm and 0.83 q/ha-cm in 2011-12 and 2012-13 respectively was found optimum as compared to I 1 , I 2 , I 4 and I 5 . The results showed that themaximum yield of wheat was obtained in treatment I 3 (IW/CPE=1.0) i.e. 37.89 q/ha and 37.9 q/ha in 2011-12 and 2012-13 respectively compared to rest of treatment with only average marginal yield reduction 1.51 q/ha in both yearunder 12.11% water saving irrigation strategy over control treatment.